Blood-retinal barrier breakdown in diabetic retinopathy - the protective role of melatonin - Djordjevic, Branka; Cvetkovic, Tatjana; Milenkovic, Jelena; Stojiljkovic, Vladana; Veljkovic, Andrej; Sokolovic, Dusan (Biologia Serbica, 2021)
Diabetes mellitus and its complications represent a global socio-economic burden with more than 450 million people affected worldwide. Diabetic retinopathy is present in over one-third of people living with diabetes and represents a leading cause of visual impairment among the working-age population. The integrity of the blood-retinal barrier (BRB) is essential for retinal neuronal health. Barrier breakdown results in fluid accumulation in the retina, macular edema, neuronal death, and vision loss. BRB breakdown may result from a disruption of the tight junctions, an up-regulation of vesicular transport across the inner or outer BRB, or by degenerative changes to the endothelial cells, the pericytes, and glia. The present review aims to discuss mediators of BRB dysfunction and molecular mechanisms of BRB breakdown in diabetes mellitus and the emerging evidence that patients with diabetic retinopathy might benefit from melatonin treatment. The data suggest that melatonin might protect ocular tissues by decreasing the production of reactive oxygen species (ROS) and pro-inflammatory mediators implicated in BRB breakdown, such as vascular endothelial growth factor (VEGF), tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β). Therefore, melatonin might be considered for treatment of ocular diseases characterized by BRB, although, the topic remains under investigation.